A structure for the yeast prohibitin complex: Structure prediction and evidence from chemical crosslinking and mass spectrometry - Back, Jaap W. (Cold Spring Harbor Laboratory Press, 2002)
The mitochondrial prohibitin complex consists of two subunits (PHB1 of 32 kD and PHB2 of 34 kD), assembled into a membrane-associated supercomplex of approximately 1 MD. A chaperone-like function in holding and assembling newly synthesized mitochondrial polypeptide chains has been proposed. To further elucidate the function of this complex, structural information is necessary. In this study we use chemical crosslinking, connecting lysine side chains, which are well scattered along the sequence. Crosslinked peptides from protease digested prohibitin complexes were identified with mass spectrometry. From these results, spatial restraints for possible protein conformation were obtained. Many interaction sites between PHB1 and PHB2 were found, whereas no homodimeric interactions were observed. Secondary and tertiary structural predictions were made using several algorithms and the models best fitting the spatial restraints were selected for further evaluation. From the structure predictions and the crosslink data we derived a structural building block of one PHB1 and one PHB2 subunit, strongly intertwined along most of their length. The size of the complex implies that approximately 14 of these building blocks are present. Each unit contains a putative transmembrane helix in PHB2. Taken together with the unit building block we postulate a circular palisade-like arrangement of the building blocks projecting into the intermembrane space.